DETERMINANTS OF CUSTOMER LOYALTY AND PROPOSING A CUSTOMER LOYALTY MODEL FOR THE BANKING SECTOR OF PAKISTAN - Afsar BILAL (Management & Marketing)
It is always costly to attract new customers, so the managers always try to find ways to retain their current customers and concentrate on different factors which enhances the customer loyalty among the customers of the organizations. This research attempts to find the factors of customer loyalty and their relationships with banking industry in one of the developing countries i.e. Pakistan. Then analyzing the relationship among different factors a model for the customer loyalty is proposed at the end of the research. In order to do this, a questionnaire is designed and validated, then based on the data which were gained from the 316 respondents' answers to the designed questionnaire, the analysis is done and the results and the relations among the factors are explained. Perceived Quality, Satisfaction, Trust, Switching Cost and Commitment are the factors which influence the Loyalty of the customers. Theses factors also influence each other as well. The relationships of different factors with each other are also studied and the SPSS software is used to analyze the data gathered from the respondents.